Intentionally Structuring the Foundation of Moral Character Values in Physical Education, Sports, and Health Learning - Subekti, Nuriska; Juhrodin; Mulyadi, Agus; Narlan, Abdul (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
Character education has become a crucial aspect of Indonesia's national education system, particularly in shaping a generation that excels not only academically but also possesses strong morality and social responsibility. In line with the Merdeka Curriculum, learning is not only focused on knowledge transfer but also on shaping students' character through the internalization of moral values. Physical Education, Sports, and Health (PESH) plays a strategic role in strengthening character because it offers students opportunities to develop values such as self-confidence, sportsmanship, honesty, discipline, teamwork, self-control, leadership, and democratic attitudes through physical activities. This study aims to explore how PESH can be designed with an intentionally structuring approach to more effectively internalize these moral values. The research involved 72 students, divided into experimental and control groups, each consisting of 36 participants. The study used a quasi-experimental design, where the experimental group received a character-based PESH learning intervention. Data collection techniques included questionnaires and observation, while data analysis was conducted using a t-test to compare the program's effectiveness between the two groups. The results of the study showed that PESH learning with a focus on moral character had a significant impact on students' personality development compared to the control group. In conclusion, the integration of moral values in PESH should be consistently applied, as it effectively shapes students with strong character and responsibility, in line with the goals of national education